2018
DOI: 10.12740/pp/64378
|View full text |Cite
|
Sign up to set email alerts
|

Ways of understanding of religious delusions associated with a change of identity on the example of identification with Jesus Christ

Abstract: Identification with Christ among psychiatric patients is an example of a complex and multifaceted phenomenon. As a delusion it includes a misidentification (change of identity) in the layer of content and, usually, grandiosity and/or paranoid traits in the formal aspect. What is more, it fits in the category of religious delusions, which are perhaps the most controversial type of delusions and as such require special sensitivity as well as knowledge beyond psychology or psychiatry. The aim of the articleis to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 15 publications
0
4
0
1
Order By: Relevance
“…According to Sieradzan (2015), studies showed that one-third of those with diagnosed psychosis with religious delusions live in Western countries. In turn, K. Dyga and R. Stupak (Dyga and Stupak 2018) indicate that the prevalence of such phenomenon among hospitalized patients is the highest in the United States (36%) and the lowest in Pakistan (6%), where a significant proportion of grandiose delusions concerns identification with God, Jesus, or Mahomet. In other studies, the frequency of religious delusions was estimated to be 21% in Germany and 6% in Japan.…”
Section: The Roots Of Religious Delusions In Schizophreniamentioning
confidence: 99%
See 3 more Smart Citations
“…According to Sieradzan (2015), studies showed that one-third of those with diagnosed psychosis with religious delusions live in Western countries. In turn, K. Dyga and R. Stupak (Dyga and Stupak 2018) indicate that the prevalence of such phenomenon among hospitalized patients is the highest in the United States (36%) and the lowest in Pakistan (6%), where a significant proportion of grandiose delusions concerns identification with God, Jesus, or Mahomet. In other studies, the frequency of religious delusions was estimated to be 21% in Germany and 6% in Japan.…”
Section: The Roots Of Religious Delusions In Schizophreniamentioning
confidence: 99%
“…More and more often, delusions are considered to be a complex and multidimensional phenomenon. Therefore, the psychological assessment process considers, for example, the number, absorption, omnipresence, distress, and the role of perception, influence on behavior, effectiveness, and strength of belief (Dyga and Stupak 2018).…”
Section: The Roots Of Religious Delusions In Schizophreniamentioning
confidence: 99%
See 2 more Smart Citations
“…В последние годы публикуется все больше работ, посвященных вопросам религиозного копинга [20][21][22][23][24], особенностям и прогностическому значению бредовых расстройств религиозного содержания. В частности, синдрома овладения и бесоодержимости [25,26], мессианского [27], апокалиптического и эсхатологического бреда [28], религиозным бредовым расстройствам в структуре юношеского эндогенного приступообразного психоза c оценкой религиозности в преморбиде и в постпсихотическом периоде [29]. Особый интерес в рамках современных исследований также представляют паранойяльные состояния, начавшиеся в подростково-юношеском возрасте с явлений метафизической интоксикации религиозного содержания [30].…”
Section: Introductionunclassified